Unanswered issues on decarbonizing the aviation industry through the development of sustainable aviation fuel from microalgae - Rony Z.I.; Mofijur M.; Hasan M.M.; Ahmed S.F.; Almomani F.; Rasul M.G.; Jahirul M.I.; Loke Show P.; Kalam M.A.; Mahlia T.M.I. (Elsevier Ltd, 2024)
Concerns have been raised about the effects of fossil fuel combustion on global warming and climate change. Fuel consumer behavior is also heavily influenced by factors such as fluctuating fuel prices and the need for a consistent and reliable fuel supply. Microalgae fuel is gaining popularity in the aviation industry as a potential source of energy diversification. Microalgae can grow in saltwater or wastewater, capture CO2 from the atmosphere and produce lipids without requiring a large amount of land. As a result, the production of oil from microalgae poses no threat to food availability. The low carbon footprint of microalgae-derived fuels has the potential to mitigate the impact of traditional aviation fuels derived from petroleum on climate change and global warming. Therefore, aviation fuels derived from microalgae have the potential to be a more environmentally friendly and sustainable alternative to conventional fuels. Gathering microalgal species with a high lipid content, drying them, and turning them into aviation fuel is an expensive process. The use of biofuels derived from microalgae in the aviation industry is still in its infancy, but there is room for growth. This study analyses the potential routes already researched, their drawbacks in implementation, and the many different conceptual approaches that can be used to produce sustainable aviation fuel from microalgal lipids. Microalgae species with fast-growing rates require less space and generate lipids that can be converted into biofuel without imperiling food security. The key challenges in algal-based aviation biofuel include decreased lipid content, harvesting expenses, and drying procedure that should be enhanced and optimized to increase process viability. 2022 Elsevier Ltd